Genetic overexpressing of GPx‐1 attenuates cocaine‐induced renal toxicity via induction of anti‐apoptotic factors. (April 2016) - Mai, Huynh Nhu; Jeong, Ji Hoon; Kim, Dae‐Joong; Chung, Yoon Hee; Shin, Eun‐Joo; Nguyen, Lan Thuy Ty; Nam, Yunsung; Lee, Yu Jeung; Cho, Eun‐Hee; Nah, Seung‐Yeol; Jang, Choon‐Gon; Lei, Xin Gen; et al.
Summary: The present study investigates the role of the glutathione peroxidase (GPx)‐1 gene in cocaine‐induced renal damage in mice. Multiple doses of cocaine increased lipid peroxidation, protein oxidation, and glutathione oxidation in the kidney of the non‐transgenic mice (non‐TG mice). The enzymatic activities of GPx and glutathione reductase were significantly decreased in non‐TG mice, whereas superoxide dismutase was increased in the early phase of cocaine exposure. Treatment with cocaine resulted in significant decreases in expression of Bcl‐2 and Bcl‐xl in the kidney of non‐TG mice, which resulted in significant increases in Bax and cleaved‐caspase 3. Consistently, cocaine‐induced tubular epithelial vacuolization and focal tubular necrosis were mainly observed in the proximal tubules in the kidneys of non‐TG mice. These renal pathologic changes were much less pronounced in GPx‐1 TG than in non‐TG mice. These results suggest that the GPx‐1 gene is a protective factor against nephrotoxicity induced by cocaine via interactive modulations between antioxidant and cell survival signaling processes.